The anxieties of a citizen class : the miracles of the true cross of San Giovanni Evangelista, Venice 1370-1480 - Petkov, Kiril, 1964- (Medieval Mediterranean ;, 2014)
In The Anxieties of a Citizen Class Kiril Petkov reveals the uses of religious symbolism and miracle metaphors for the expression and alleviation of the social anxieties accompanying the formation of the cittadini originarii, the upper-middle class of fifteenth-century Venice.